#22: Clinical Significance of Human Herpes Virus 6 Positivity in Children. (28th June 2021) - Kinler, Zachary K; Inagaki, Kengo; Galloway, Regina; Palmer, April L; Santos, Roberto P
Abstract: Background: Human Herpes Virus 6 (HHV6) is a common childhood disease that is typically mild, however, cases where it is the causative agent of meningitis/encephalitis (ME) have been reported. The treatment for HHV6 ME consists of ganciclovir, which is associated with bone marrow suppression and renal insufficiency. While the clinical significance of the presence of HHV6 in cerebrospinal fluid (CSF) in adults has been studied, there is a paucity of research on the clinical significance of HHV6 in the CSF of children with ME. We want to determine if there is clinical significance to HHV6 positivity in the CSF of children. Methods: 20 patients were included whose CSF tested positive for HHV6 on the CSF ME panel from Jan 1, 2017 to May 20, 2020. We obtained a sample of 80 patients whose CSF tested negative for every pathogen on the same CSF ME panel from the same period. Logistic regression was used based on age, sex, race/ethnicity, admission to neonatal intensive care unit (NICU)/pediatric intensive care unit (PICU), clinical presentation, and presence of abnormalities on neuroimaging to determine the propensity score matching (PSM) for each patient. (Table I) The HHV6 positive patients were matched with patients who tested negative for every pathogen on the panel at a 1:1 ratio and within a caliper size of 0.25. The odds ratio (OR) of neurological sequelae at discharge was determined by performing a logistic regression based on HHV6 status in both the group with PSM and without PSM. The length of stay between the HHV6 positive group and the control group were compared with and without PSM using Mann-Whitney U test with p<0.05 considered significant Results: The OR for HHV6 positivity and experiencing neurological sequelae is 1.35 with a 95% confidence interval (CI) 0.133, 13.721 (p=0.799) when compared to the control group without PSM. The OR for HHV6 positivity and experiencing neurological sequelae is 1 with a 95% CI 0.063, 15.988 (p=0.549) when compared to the control group with PSM. Table I shows the neurological sequelae between the HHV6 positive group, control group without PSM and the control group with PSM. It shows the Mann-Whitney U test comparing HHV6 status to the median length of hospital stay in both unmatched- and matched cohorts. We failed to reject the null hypothesis that there was a difference in the median length of hospital stay between HHV6 positive patients and all negative patients with and without PSM. Conclusion: There is no clinical significance of HHV6 detection on the CSF ME panel in children as well as no statistical significance between the median length of hospital stay among HHV6 positive patients and all negative patients. Further, 10% of the HHV6 positive patients were inappropriately started on ganciclovir. Development of a consensus statement is in place regarding releasing the result of a positive HHV6 from the ME panel only among immunocompromised children to prevent inappropriate antiviral therapy.